Strengthening Muslim Women’s Fiqh Literacy in Kalukubodo Village through Fasting Jurisprudence Education: A Practical Study of Menstruation, Postpartum Bleeding, Qaḍā’, and Fidyah Rulings: PENGUATAN LITERASI FIKIH MUSLIMAH DESA KALUKUBODO MELALUI EDUKASI FIKIH PUASA: KAJIAN PRAKTIS HUKUM HAID, NIFAS, QAḌĀ’, DAN FIDYAH - Eka Syahriani; Muhammad Fachmi; Husnul Khatimah Mujahidah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2026)
This community service program aimed to strengthen women’s fiqh literacy in Kalukubodo Village through practical education on fasting jurisprudence, particularly the rulings related to menstruation, postpartum bleeding, qada’, and fidyah. The main participants of this program were Muslim women in Kalukubodo Village, Galesong Selatan District, Takalar Regency, including young women and mothers who required structured religious guidance before Ramadan. The program employed a Participatory Action Research approach by involving the community in problem identification, implementation, discussion, and evaluation. Data were collected through direct observation, participant involvement, coordination with local authorities, and in-depth discussions with women representatives. The results showed that the interactive taklim model encouraged active participation and helped participants clarify practical issues related to fasting obligations. Participants demonstrated high enthusiasm, particularly during the question-and-answer session, which indicated the relevance of the topic to their daily religious practices. This program revealed that community-based fiqh education with dialogical and case-based learning can become an effective strategy to strengthen women’s understanding of Islamic fasting rulings.